Exploring the anti-cancer potential of coumarin derivatives targeting COX-2 inhibitors - Thanh Tin Le; Y Thien Vu; Hieu Minh Doan; Bao Le (Ho Chi Minh City Open University Journal of Science - Engineering and Technology)
Overexpression of cyclooxygenase-2 (COX-2) plays a crucial role in cancer therapy. In this study, we investigated the role of two coumarin derivatives with the chlorobenzylamide group in inhibiting COX-2 activity and growth inhibition of cancer cells. The effect of synthesized 2a and 2b coumarin derivatives on COX-2 enzyme was investigated in vitro. Besides that, A549, HT-29, MDA-MMB-231, and HeLa tumor cell lines were used to evaluate potential inhibition growth using the MTT assay. According to the results, two synthesized compounds showed an inhibitory effect on COX-2 enzymes. In particular, 2a exhibited the best activity with an IC50 value of 49.54μM on COX-2. The 2a and 2b exhibited a noteworthy dose-dependent inhibitory growth activity against all the tested cancer cell lines, indicating their broad-spectrum anti-cancer properties. Based on the in vitro data, we strongly recommend this new coumarin-o-chlorobenzylamide as a preclinical development candidate for novel anti-cancer agents targeting COX-2 inhibition.